Organocatalytic oxidative synthesis of C2-functionalized benzoxazoles, naphthoxazoles, benzothiazoles and benzimidazoles. Issue 3 (17th January 2019) - Kaldhi, Dhananjaya; Vodnala, Nagaraju; Gujjarappa, Raghuram; Nayak, Subhashree; Ravichandiran, V.; Gupta, Sreya; Hazra, Chinmoy K.; Malakar, Chandi C.
Graphical abstract: Highlights: No sensitive and hazardous reagents were used. Reaction excludes the involvement of precious metals, additives, ligands and radical initiators. Reaction proceeds without formation of any toxic side products. Developed method utilizes 3-nitropyridine as organocatalyst under aerobic conditions. Potential application for the synthesis of a broad range of compounds in excellent yields.